The Komparasi Tafsir Adwa’ Albayan Karya Asy-Syanqithi dan Ma’alim Al-Tanzil Karya Al-Husein Ibn Mas’ud Al-Baghawi (Studi Analisis Qs. Al-Ma’idah [5]: 6) - Kartini Fujiyanti Agustin (LPPM Sekolah Tinggi Ilmu Ushuluddin Darussalam Bangkalan Madura, 2023)
This study aims to dissect the concepts and methods of bil matsur interpretation of the two interpretations, namely the tafsir adwa' al-Bayan by asy-Syinqithi and the tafsir Ma'alim al-Tanzil by al-Baghawi so that the points of similarity and differences between the two are found. This research is qualitative with library data and primary sources in Qs. Al-Ma'idah [5]: 6 which discusses ablution. This research is a literature research on the methodology of interpretation bil matsur written by the two interpreters. Comparative studies were conducted to uncover similarities and differences between the two. Researchers revealed that the two figures share the same line of thought. One of them structured this science and the other developed it to be more perfect.